Perancangan Sistem Kontrol Genetic-Fuzzy: Studi Kasus Pada Pengendalian Top And Side End Point Composition Dan Bottom Reflukstemperature Pada Distillation Column - Meilia Safitri; Aris Triwiyatno; Wahyudi Wahyudi (Departemen Teknik Elektro, Universitas Diponegoro, 2012)
Genetic-Fuzzy Control is one of the control technique which is use to solve the non-linear problems by combinating two control methods, Fuzzy Logic Controller and Genetic Algorithm. Genetic algorithm is use to overcome the difficulties in determining the membership function parameter that can optimally work on Fuzzy Logic Controller. In this paper Genetic-Fuzzy control is used to control Shell Heavy Oil Fractionator which is mulvariable system with 3 input and 3 output. Decoupling have the function to reduce interaction between input and output that are not paired. Keyword : Genetic-Fuzzy control, distillation column, decoupling, MATLAB Simulink, Multivariable system